XAF1 directs glioma response to temozolomide through apoptotic transition of autophagy by activation of ROS-ATM-AMPK signaling. Issue 1 (7th February 2022) - Lee, Min Goo; Choi, Zisun; Lim, Na Jung; Lim, Ji Sun; Lee, Kyung Woo; Ko, Kyung Phil; Ryu, Byung Kyu; Kang, Shin Hyuk; Chi, Sung Gil
Abstract: Background: X-linked inhibitor of apoptosis-associated factor 1 (XAF1) is a tumor suppressor that is commonly inactivated in multiple human cancers. However, its role in the pathogenesis and therapeutic response of glioma is poorly characterized. Methods: XAF1 activation by temozolomide (TMZ) and its effect on TMZ cytotoxicity were defined using luciferase reporter, flow cytometry, and immunofluorescence assays. Signaling mechanism was analyzed using genetic and pharmacologic experiments. In vivo studies were performed in mice to validate the role of XAF1 in TMZ therapy. Results: Epigenetic alteration of XAF1 is frequent in cell lines and primary tumors and contributes to cancer cell growth. XAF1 transcription is activated by TMZ via JNK-IRF-1 signaling to promote apoptosis while it is impaired by promoter hypermethylation. In tumor cells expressing high O 6 methylguanineDNA methyltransferase (MGMT), XAF1 response to TMZ is debilitated. XAF1 facilitates TMZ-mediated autophagic flux to direct an apoptotic transition of protective autophagy. Mechanistically, XAF1 is translocated into the mitochondria to stimulate reactive oxygen species (ROS) production and ataxia telangiectasia mutated (ATM)-AMPactivated protein kinase (AMPK) signaling. A mutant XAF1 lacking the zinc finger 6 domain fails to localize in the mitochondria and activate ROS-ATMAMPK signaling and autophagy-mediated apoptosis. XAF1restored xenograft tumors display a reduced growth rate and enhanced therapeutic response to TMZ, which is accompanied with activation of ATMAMPK signaling. XAF1 expression is associated with overall survival of TMZ treatment patients, particularly with low MGMT cancer. Conclusions: This study uncovers an important role for the XAF1ATMAMPK axis as a linchpin to govern glioma response to TMZ therapy.